Innovative Vocabulary Learning Through Games-Based Learning at SMKN 3 Parepare - Nurul Faradillah; Isumarni Isumarni; Nurhikmah Nurhikmah; Yadinda Mahardika Darwis Putri; Septita Puteri Namirta; Sam Hermansyah; Nanda Putri; Winda Aprilia (Edumaspul: Jurnal Pendidikan, 2024)
Vocabulary is a fundamental aspect of language proficiency, serving as a critical foundation for communication, comprehension, and academic success. However, many vocational high school students face challenges in mastering English vocabulary due to teaching methods that often overlook individual differences in learning needs and abilities. This study explores the implementation of the "Learning Vocabulary" program, designed as part of a teaching assistance initiative at SMKN 3 Parepare, to improve students' vocabulary mastery through personalized and game-based learning methods.The program integrates weekly vocabulary activities involving nouns, adverbs, verbs, and adjectives, utilizing interactive games such as Word Guessing Game, Memory Match, Scrabble, and Role-Playing. These methods aim to foster student motivation and active engagement while addressing individual needs. Data were collected through vocabulary tests, observations, and interviews, and analyzed descriptively.The results reveal significant improvements in students' vocabulary mastery and motivation, highlighting the effectiveness of games-based learning in creating a fun and interactive learning environment. Challenges, including initial resistance to new methods, were addressed through consistent implementation and student adaptation. This study concludes that the "Learning Vocabulary" program, with its focus on individualized and engaging activities, is an effective model for enhancing vocabulary learning in vocational schools.